DERADIKALISASI PENAFSIRAN AL-QUR’AN - Arifin, Mohammad Zaenal (IAIN Kediri, 2015)
Tafsir is an attempt to understand the QurÃ¢â‚¬â„¢an from all its aspects according to the human capacity. TheÃ‚Â products of tafsir certainly plays a significant role in determining how public will understand Islam. Therefore,Ã‚Â a QurÃ¢â‚¬â„¢anic interpretation should be built upon a noble goal, which is to provide an ontological view that theÃ‚Â QurÃ¢â‚¬â„¢an is a Ã¢â‚¬Å“Book of RaÃ¡Â¸Â¥mahÃ¢â‚¬Â encouraging the people to create a tolerant and moderate society. This paper isÃ‚Â an attempt to break the chain that led to the emergence of reconstructing radical interpretation of the QurÃ¢â‚¬â„¢an.Ã‚Â It will first present a critique on those radical interpretations, and then reconstruct them within the frameworkÃ‚Â of the QurÃ¢â‚¬â„¢anÃ¢â‚¬â„¢s Ã¡Â¹Â£Ã„ÂliÃ¡Â¸Â¥ li kulli zamÃ„Ân wa makÃ„Ân.Keywords: Radikalisasi, Deradikalisasi, Ã¡Â¹Â£Ã„ÂliÃ¡Â¸Â¥ li kulli zamÃ„Ân wa makÃ„Ân